New Recent Trends in Agenda Setting Studies n The Arab World - Mohamed, Hamza Saad (ALBAHITH ALALAMI, 2019)
This study aims to examine the main features of the new trends in agenda studies using the secondary analytic approach in analyzing the newest studies in agenda-setting issues from 2007 till 2017, in addition to the quantitative approach.The researcher has analyzed 110 studies -75 foreign and 35 Arabic - to determine, describe and evaluate the key research trends which came in Arabic and foreign agenda-setting studies. The results confirmed that studies of the agenda theory are increasing steadily worldwide with diversity in the theoretical trends and used research tools. In addition, primary studies focus on content analysis and the survey approach (method). Also, most Arabic agenda-setting studies used the traditional methods and known research tools such as content analysis and survey, contrary to the foreign studies conducted in the same field where they were characterized by the different research teams specializing in many scientific branches. The study recommends more cooperation among Arab researchers and the re-survey of the research map in fields of agenda studies. It also recommends giving more attention to comparative studies, revising the used methods and tools and focusing more on interdisciplinary studies through different timespans (periods).